Signal When Through. (America Magazine: The Jesuit Review of Faith & Culture, 1960)
The article reports on the predictions of a prophetic researcher regarding the advent of an advanced communication system. It states that in twenty years, people will be making worldwide calls by a telephone that is complete with a computer which automatically translates any language that is familiar to the caller. It notes that the conversation can be automatically translated into Russian, French, or English. It concludes that all that is needed is a machine that knows grammar good.